2006
DOI: 10.1007/s10548-006-0267-4
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Visual Evoked Potentials: Distributed Local Sources and Wave-Like Dynamics Are Sensitive to Flicker Frequency

Abstract: Steady-state visual evoked potentials (SSVEPs) are used in cognitive and clinical studies of brain function because of excellent signal-to-noise ratios and relative immunity to artifacts. SSVEPs also provide a means to characterize preferred frequencies of neocortical dynamic processes. In this study, SSVEPs were recorded with 110 electrodes while subjects viewed random dot patterns flickered between 3 and 30 Hz. Peaks in SSVEP power were observed at delta (3 Hz), lower alpha (7 and 8 Hz), and upper alpha band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
136
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(157 citation statements)
references
References 40 publications
(77 reference statements)
13
136
1
2
Order By: Relevance
“…Twenty-six participants took part in the experiment (18 women, 8 men, median age 23, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Participants were recruited among students and staff of the university and were naïve to the aims of the study.…”
Section: Participantsmentioning
confidence: 99%
“…Twenty-six participants took part in the experiment (18 women, 8 men, median age 23, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Participants were recruited among students and staff of the university and were naïve to the aims of the study.…”
Section: Participantsmentioning
confidence: 99%
“…SS-EPs elicited by visual, auditory, and vibrotactile stimuli have been shown to originate mainly from the corresponding primary sensory cortices (Snyder, 1992;Pantev et al, 1996;Kelly et al, 1997;Kelly and Folger, 1999;Srinivasan et al, 2006;Giabbiconi et al, 2007). Hence, it may be hypothesized that nociceptive SS-EPs reflect the entrainment of neurons that are at least partly involved in early, modality-specific, nociceptive processing.…”
Section: Functional Significance Of Ss-epsmentioning
confidence: 99%
“…These steady-state responses are thought to result from an entrainment or resonance of a population of neurons responding to the stimulus at the frequency of stimulation (Herrmann, 2001;Muller et al, 2001;Vialatte et al, 2010). A large number of studies have used this approach to explore the cortical activity involved in processing other sensory modalities and have shown that this technique is effective to capture neural activity related to sensory processing, originating mainly from primary sensory cortices (Snyder, 1992;Pantev et al, 1996;Kelly and Folger, 1999;Tobimatsu et al, 1999;Plourde, 2006;Srinivasan et al, 2006;Giabbiconi et al, 2007;Vialatte et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Steady-state visual stimuli may be used to probe EEG responses: recent work comparing EEG and fMRI of human participants exposed to flickering light found that medial frontal cortex metabolic activity depended on the temporal frequency of visual input implying that during visual stimulation, input frequency can be used to activate distinct functional networks [146]. Indeed the use of visual flicker to purposefully modify cortical activity in order to improve memory has been explicitly tested [169,170].…”
Section: Visual Entrainmentmentioning
confidence: 99%